Gender Battles in Thai Ghost Films of Buppah Rahtree Sequels: The Transformation of Gender Authority - Suphap, Aphiradi (Advances in Humanities and Contemporary Studies, 2020)
This academic article intends to demonstrate how the power transforms from men to woman in the film of Buppah Rahtree’s sequels. Buppah Rahtree’s sequels are the Thai ghost films by dir. Yuhtlert Sippapak. These Thai ghost sequels are different from other Thai ghost films in which they break free from both American and Thai horror films’ conventions. The female protagonist, the ghost of Buppah, takes turn to possess her own weapon, the folding shave razor which symbolises the phallic symbol, as the tool to take a revenge on her victims especially men. Her weapon possession is contrasted to the slasher films’ norms in which the killers are men and men are the ones who carry the weapons around to kill the female victims. Although the female protagonist has been oppressed for the first half of the film, the authority is in the hand of woman for the rest of the stories. The female major character, hence, appears to have more power than men: Buppah is the ghost and the killer who gains more victory over the victimized men.